(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article studies the forms of modern women’s outerwear, the analysis of the fabrics used, the physical, mechanical and operational properties of the materials, and as a result of these analyses, a new range of modern and complex-shaped dresses for women using national patterns was developed.